(untitled) (International Conference on Computers in Education, 2017)
In this study, we developed an interactive simulation which can provide authentic observation experience on precipitation reaction by embedding video clips of the actual experiment result. The purpose of this development was to assist students in more authentic observation and modeling on the precipitation reaction. The simulation was built with Flash and ActionScript to runs on wide-ranging devices regardless of operating system. The development process of a simulation through design seminars to reflects the diverse perspectives of teachers and science education experts. Then, we confirmed the validity of the development through the expert evaluation of two experts of science education and four teachers who did not participate in the design seminars. Attempting to introduce new characteristics into science simulation can be attributed to extending the field of simulation design on science education. This study is thought to be useful to come up with a design form suitable for science digital textbooks.